50.9k views
4 votes
HELP PLZ HURRY!!!!!!!!!

HELP PLZ HURRY!!!!!!!!!-example-1
User Ariadna
by
5.0k points

1 Answer

2 votes

Answer:

You need to memorize an

Elimination method

Multiply the first equation by -3,and multiply the second equation by 1:

−3(3x+y=−9)

1(9x+4y=−33)

Explanation:

Answer:

B. x=-1, y=-6

9x+4y=-33

3x+y=-9

9x+4y=-33

-4(3x+y=-9)

9x+4y=-33

-12x-4y=36

------------------

-3x+0=3

x=-1

plug in the x to either original question

3(-1)+y=-9

y=-6

final answer: x=-1, y=-6

User Victor Yarema
by
4.4k points